2013
DOI: 10.1155/2013/918490
|View full text |Cite
|
Sign up to set email alerts
|

Critical Phenomena in Higher Curvature Charged AdS Black Holes

Abstract: In this paper we have studied the critical phenomena in higher curvature charged black holes in the anti-de Sitter (AdS) space-time. As an example we have considered the third order Lovelock-Born-Infeld black holes in seven dimensional AdS space-time. We have analytically derived the thermodynamic quantities of the system. Our analysis revealed the onset of a higher order phase transition in the black hole leading to an infinite discontinuity in the specific heat at constant charge at the critical points. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 92 publications
1
18
0
Order By: Relevance
“…More interesting discoveries were obtained for the charged AdS black holes [6,7], where it was found that a first order small black hole and big black hole phase transition is allowed which is superficially analogous to a liquid-gas phase transition of the van der Waals fluid. This superficial reminiscence was also observed in other AdS backgrounds [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 73%
“…More interesting discoveries were obtained for the charged AdS black holes [6,7], where it was found that a first order small black hole and big black hole phase transition is allowed which is superficially analogous to a liquid-gas phase transition of the van der Waals fluid. This superficial reminiscence was also observed in other AdS backgrounds [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 73%
“…Different from the RN-AdS black hole, there are two van der Waals-like critical points identified at different temperatures. The critical phenomena of Born-Infeld AdS black holes and higher curvature charged AdS black holes were investigated in [21][22][23], where the critical exponents were also examined. Treating the cosmological constant as a thermodynamic pressure and its conjugate quantity as a thermodynamic volume, the critical behavior and P -V criticality of a charged AdS black hole is reexamined [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The asymptotically AdS charged black holes admit a gauge duality description via a dual thermal field theory. This dual description suggests that charged AdS black holes exhibit a critical behavior in the Q − φ diagram which is reminiscent of the liquid-gas phase transition a e-mail: xuweifuture@mail.nankai.edu.cn b e-mail: physicshx@gmail.com c e-mail: lzhao@nankai.edu.cn in a Van der Waals system [6][7][8][9][10][11][12][13], where Q and φ denote the electric charge and potential, respectively.…”
Section: Introductionmentioning
confidence: 99%